2022
DOI: 10.1111/nph.18629
|View full text |Cite
|
Sign up to set email alerts
|

The cost of self‐promotion: ecological and demographic implications of the mentor effect in natural plant populations

Abstract: Under the mentor effect, compatible heterospecific pollen transfer induces self-pollen germination in otherwise self-incompatible plants. The mentor effect could be considered a novel mode of reproductive interference if it negatively impacts fitness. Yet to date, this phenomenon has predominately been investigated under experimental conditions rather than in situ. We address this gap in natural populations of the self-incompatible native dandelion, Taraxacum ceratophorum, where selfing only occurs in associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…For our species, self-incompatible species showed an overall lower seed set, while breeding system did not affect seed number or HPI in any way. Self-compatibility might play a role especially in a natural community, where HP can act through the mentor effect (de Nettancourt, 1997), and allowing for self-fertilization even in self-incompatible flowers, with consequent ovule abortion (Lynn, Sullivan, & Galen, 2022). In our study we showed how self-incompatible species are less likely to produce seeds even when enough pollen is present.…”
Section: Discussionmentioning
confidence: 50%
“…For our species, self-incompatible species showed an overall lower seed set, while breeding system did not affect seed number or HPI in any way. Self-compatibility might play a role especially in a natural community, where HP can act through the mentor effect (de Nettancourt, 1997), and allowing for self-fertilization even in self-incompatible flowers, with consequent ovule abortion (Lynn, Sullivan, & Galen, 2022). In our study we showed how self-incompatible species are less likely to produce seeds even when enough pollen is present.…”
Section: Discussionmentioning
confidence: 50%